Estimation in the semantic structure of the word (Eurasian Journal of Philology Science and Education, 2015)
The basic terms of linguistic nature of estimative meaning, its relationship with such subjective, «anthropocentric » categories, as emotiveness, expressiveness are considered in this article. The main items of estimativesemantics nomination are adjectives. There are two types of semantic components in the meanings of adjectives: a denotative component that transmits a general logical meaning, enclosed in a word, and connotative component - its additional gradations, where such micro components as emotiveness, estimation and intensity are concentrated. The author identified 3 types of words in accordance with the nature of semantics estimation and its place in the semantic structure of the word and contextual dependence: lexical units with descriptive meaning (type D), with estimative meaning (type E), words with descriptive and estimative components in meaning (type DE), the last type is divided into two subtypes: with descriptive dominant component (subtype DE-1) and the estimative dominant component (subtype DE 2).
Keywords: estimative semantics; word meaning; denotative semantics; connotation; emotional breadth; estimation; expressivity; estimate scale; sustainable estimation; emotional estimation.